Um novo escalonador com controle de admissão de conexão para o padrão IEEE 802.16 com garantia de limite de atraso - Dosciatti, Eden Ricardo (2010)
The IEEE 802.16 Working Group on Broadband Wireless Access is developing a standard for broadband wireless access networks in Metropolitan Area Network (MAN), also know as WiMAX. One of the features of the MAC (Media Access Control) layer is that it was designed to differentiate service among traffic categories with different multimedia requirements. Based on these assumptions and considering that the standard does not specify a scheduling algorithm, a new scheduler with admission control connection has been proposed based on Latency-Rate (LR) server theory and system characteristics specified by the standard for systems using the WirelessMAN-OFDM (Orthogonal Frequency Division Multiplexing) air interface. The proposed scheduling algorithm calculates the Time Frame (TF) in order to maximize the number of stations allocated in the system while guarantee the delay required for each user. Properties of this proposal have been investigated theoretically and through simulations. A set of simulations is presented with streams of Constant Bit Rate (CBR) and Variable Bit Rate (VBR) and performance comparisons with different delays and different TFs. The results showed that the upper limit of delay can be achieved by a variety of loads in the network, optimizing the bandwidth.